EMOTIONAL INTELLIGENCE AMONG STUDENTS AT UNIVERSITY OF MEDICINE AND PHARMACY, HUE UNIVERSITY AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the emotional intelligence of students at University of Medicine and Pharmacy, Hue University and to identify factors associated with emotional intelligence.Methods: A cross-sectional descriptive study was conducted among 710 second- to fourth-year students. Emotional intelligence was assessed using the short form of the TEIQue-SF, with a Cronbach’s Alpha of 0.81. Multivariable linear regression was employed to examine factors associated with emotional intelligence.Results: The mean emotional intelligence score was 4.24 ± 0.48 points. Among its components, the “well-being” domain had the highest mean score (4.50 ± 0.72 points). Multivariable linear regression analysis indicated that emotional intelligence was significantly associated with age (B = 0.043; 95% CI: 0.00-0.077; p = 0.012), gender (B = 0.091; 95% CI: 0.018-0.164; p = 0.015), place of residence (B = 0.132; 95% CI: 0.037-0.227; p = 0.006), and level of interest in the field of study (moderate interest: B = 0.188; 95% CI: 0.001-0.375; p = 0.049; high interest: B = 0.320; 95% CI: 0.132-0.508; p < 0.001).Conclusion: Integrating emotional intelligence development into the curriculum is recommended, with particular attention to younger students, males, and those with less favorable living conditions. Enhancing academic counseling and career orientation may improve students’ interest in their field of study and promote better mental health outcomes.
Keywords: Emotional intelligence, medical students, associated factors, higher education.